The effects of strength of religious faith on post-traumatic growth in patients with epilepsy - Turan, Gulcan Bahcecioglu; Yildiz, Esra; Ozer, Zulfunaz (Academic Press Inc Elsevier Science, 2023)
Aim: This study was conducted to examine the effects of strength of religious faith on post-traumatic growth in patients with epilepsy. Method: This cross-sectional and correlational study was conducted with 112 participants who were admitted to the neurology outpatient clinic of a university hospital in eastern Turkey, who met the research criteria and agreed to participate in the study. The data were collected by using ''Descriptive Information Form, ''Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ), and ''Post-traumatic Growth Inventory (PTGI). Santa Clara Strength of Religious Faith Questionnaire SCRFSQ has a maximum strength of faith score of 40 points and the PGTI has a maximum growth after a traumatic event score of 105 points. Results: Mean SCSRFQ total score of the participants was found to be 31.04 +/- 5.17. Mean PTGI total score was found to be 60.54 +/- 16.50. As a result of the regression analysis, it was found that the independent variable affected the dependent variable PTGI total score significantly (F-(1,F-110) = 13.999, p = 0.000). It was also found that the independent variable affected the PTGI total score positively (beta = 0.336) and explained 11% of the PTGI total score (p < 0.001). Conclusion: It was found that the participants had high strength of religious faith score and moderate post-traumatic growth score. It was found that post-traumatic growth increased as strength of religious faith increased. (c) 2023 Elsevier Inc. All rights reserved.
Keywords: Strength of religious faith; Epilepsy; Patient; Post-traumatic growth